Quantitative assessment of retinal vasculature changes in systemic lupus erythematosus using wide-field OCTA and the correlation with disease activity - Meng, Lihui; Chen, Lulu; Zhang, Chenxi; Chen, Huan; Yang, Jingyuan; Wang, Yuelin; Zhang, Wenfei; Cheng, Shiyu; Zhao, Qing; Zhao, Xinyu; Chen, Youxin (Frontiers in Immunology, 2024)
Purpose: To assess the retinal vasculature changes quantitatively using wide-field optical coherence tomography angiography (OCTA) in systemic lupus erythematosus (SLE), and explore its correlation with systemic clinical features. Design: Prospective, cross-sectional, observational study. Participants and controls: Patients with SLE who presented to the Ophthalmology Department of Peking Union Medical College Hospital from November 2022 to April 2023 were collected. The subjects were divided into retinopathy and without retinopathy groups. Age and gender matched healthy subjects were selected as controls. Methods: Patients with SLE and control subjects were imaged with 24×20 mm OCTA scans centered on the fovea and 6×6 mm OCTA scans centered on the optic disc. The sub-layers of OCTA images were stratified by the built-in software of the device and then the retinal thickness and vessel density were measured automatically. The characteristics of retinal OCTA parameters of SLE and its correlation with systemic clinical indicators of patients without retinopathy were analyzed. Main Outcome Measures: OCTA parameters, visual acuity, intraocular pressure and systemic clinical indicators of patients such as disease activity index, autoimmune antibodies, inflammatory marker levels were collected. Results: A total of 102 SLE patients were included, 24 of which had retinopathy and 78 had retina unaffected. Wide-field OCTA could effectively detect retinal vascular obstruction, non-perfusion area, and morphological abnormalities in patients with lupus retinopathy. SLE patients without retinopathy had significantly higher retinal superficial vessel density (SVD) in foveal (P=0.02), para-foveal temporal (P=0.01), nasal (P=0.01), peripheral foveal temporal (P=0.02) and inferior areas (P=0.02), as well as subregion temporal (P=0.01) and inferior areas (P=0.03) when comparing with healthy controls (n=65 eyes from 65 participants). The area under curve (AUC) value of subregion inferior SVD combined parafoveal temporal SVD was up to 0.70. There was a significantly positive correlation between SVD and disease activity in SLE without retinopathy group. Patients with severe activity had the most significant increase in SVD. Conclusion: Wide-field OCTA can provide a relative comprehensive assessment of the retinal vasculature in SLE. In the absence of pathological changes of retina, the SVD was significantly increased and was positively correlated with disease activity of SLE.